HIGH VOLTAGE MEASUREMENT AMPLIFIER - Довгаль, Артем (Modern engineering and innovative technologies, 2023)
This article discusses the construction of a high-voltage measuring amplifier and a model capable of changing the working range of a single voltage. Schemes and diagrams have been translated.